Severe dyslipidemia and immune activation in HIV patients with dysglycemia. Issue 5 (2nd September 2016) - Jin, Changzhong; Ji, Shujing; Xie, Tiansheng; Höxtermann, Stefan; Fuchs, Wolfgang; Lu, Xiangyun; Wu, Haibo; Cheng, Linfang; Skaletz-Rorowski, Adriane; Brockmeyer, Norbert H.; Wu, Nanping
Abstract : Background and Objective: Diabetes mellitus (DM) is common in human immunodeficiency virus (HIV)-infected patients. However, the relationship between dysglycemia, lipid metabolism, and immune activation in HIV patients is poorly understood. Methods: We retrospectively analyzed the clinical data of 180 HIV patients, including 153 patients undergoing highly active antiretroviral therapy (HAART) and 27 HAART-naive patients. DM was defined as fasting serum glucose levels ≥126 mg/dl, and impaired fasting glucose (IFG) was defined as serum glucose levels of 101–125 mg/dl at two different time points. Lipid metabolic indexes were measured. CD4+, CD8+, and CD8+ HLA-DR+ T cells were determined by flow cytometry. Results: IFM and DM percentages were higher in the HAART group than in the HAART-naive group (59.5% vs. 48.1% and 21.6% vs. 7.4%, respectively; p < 0.01). Additionally, DM percentage was high in patients receiving HAART containing protease inhibitors. Serum levels of triglycerides and very low-density lipoprotein cholesterol were higher in IFG and DM HAART patients than in euglycemic HAART patients ( p < 0.05). Serum triglyceride levels were higher in HAART-naive DM patients than in other patients ( p < 0.05). CD8+ and CD8+ HLA-DR+ cell counts were higher in IFG and DM HAART patients than in euglycemic HAART patients ( p < 0.05). Ordinal logistic regression analysis suggested that TRIG, VLDL, CD8, and HAART were predictors of glucose metabolic disorders. Conclusion: HIV patients with hyperglycemia have severe dyslipidemia and immune activation, and HAART is an important impact factor of glucose and lipid metabolic disorders.